Incorporating single‐side sparing in models for predicting parotid dose sparing in head and neck IMRT. Issue 2 (28th January 2014) - Yuan, Lulin; Wu, Q. Jackie; Yin, Fang‐Fang; Jiang, Yuliang; Yoo, David; Ge, Yaorong
Abstract : Purpose: : Sparing of single‐side parotid gland is a common practice in head‐and‐neck (HN) intensity modulated radiation therapy (IMRT) planning. It is a special case of dose sparing tradeoff between different organs‐at‐risk. The authors describe an improved mathematical model for predicting achievable dose sparing in parotid glands in HN IMRT planning that incorporates single‐side sparing considerations based on patient anatomy and learning from prior plan data. Methods: : Among 68 HN cases analyzed retrospectively, 35 cases had physician prescribed single‐side parotid sparing preferences. The single‐side sparing model was trained with cases which had single‐side sparing preferences, while the standard model was trained with the remainder of cases. A receiver operating characteristics (ROC) analysis was performed to determine the best criterion that separates the two case groups using the physicianˈs single‐side sparing prescription as ground truth. The final predictive model (combined model) takes into account the single‐side sparing by switching between the standard and single‐side sparing models according to the single‐side sparing criterion. The models were tested with 20 additional cases. The significance of the improvement of prediction accuracy by the combined model over the standard model was evaluated using the Wilcoxon rank‐sum test. Results: : Using the ROC analysis, the best single‐side sparing criterion is (1) the predicted median dose of one parotid is higher than 24 Gy; and (2) that of the other is higher than 7 Gy. This criterion gives a true positive rate of 0.82 and a false positive rate of 0.19, respectively. For the bilateral sparing cases, the combined and the standard models performed equally well, with the median of the prediction errors for parotid median dose being 0.34 Gy by both models ( p = 0.81). For the single‐side sparing cases, the standard model overestimates the median dose by 7.8 Gy on average, while the predictions by the combined model differ from actual values by only 2.2 Gy ( p = 0.005). Similarly, the sum of residues between the modeled and the actual plan DVHs is the same for the bilateral sparing cases by both models ( p = 0.67), while the standard model predicts significantly higher DVHs than the combined model for the single‐side sparing cases ( p = 0.01). Conclusions: : The combined model for predicting parotid sparing that takes into account single‐side sparing improves the prediction accuracy over the previous model.